Use of artificial genetic algorithm for genetic improvement of cattle in Angola - Pinto, Francisco João (Revista Ciencias Técnicas Agropecuarias, 2025)
The general objective of this work is to use the artificial genetic algorithm as a tool for the genetic improvement of cattle in Angola.The use of this tool for genetic improvement of cattle aims to increase meat and milk production through the selection and crossing of animals with desirable characteristics.The Angolan government has invested in livestock development programs, including cattle restocking and genetic improvement.Genetic improvement of livestock in Angola, as in other regions, seeks to improve the genetic characteristics of animals to increase the production of meat, milk, or other desired characteristics, such as precocity and meat quality. This is done through the selection of animals with good characteristics, the use of techniques such as artificial insemination, and the management of herds to ensure genetic evolution over time. Thus, genetic improvement has contributed not only to generating a more productive and precocious animal, but also to gain resistance to adverse environments, diseases and parasites.The results demonstrate that artificial insemination has been the most successful and effective reproduction biotechnology in animal production in Angola, being responsible for genetic increase rates in dairy farming of around 1.0 to 1.5%.It has revolutionized the commercial dairy cattle population in recent years, allowing the dissemination of superior genotypes on a large scale.